Experimental observations of flow instabilities and rapid mixing of two dissimilar viscoelastic liquids - Gan, Hiong Yap (2013)
Viscoelastically induced flow instabilities, via a simple planar microchannel, were previously used to produce rapid mixing of two dissimilar polymeric liquids (i.e. at least a hundredfold different in shear viscosity) even at a small Reynolds number. The unique advantage of this mixing technology is that viscoelastic liquids are readily found in chemical and biological samples like organic and polymeric liquids, blood and crowded proteins samples; their viscoelastic properties could be exploited. As such, an understanding of the underlying interactions will be important especially in rapid microfluidic mixing involving multiple-stream flow of complex (viscoelastic) fluids in biological assays. Here, we use the same planar device to experimentally show that the elasticity ratio (i.e. the ratio of stored elastic energy to be relaxed) between two liquids indeed plays a crucial role in the entire flow kinematics and the enhanced mixing. We demonstrate here that the polymer stretching dynamics generated in the upstream converging flow and the polymer relaxation events occurring in the downstream channel are not exclusively responsible for the transverse flow mixing, but the elasticity ratio is also equally important. The role of elasticity ratio for transverse flow instability and the associated enhanced mixing were illustrated based on experimental observations. A new parameter Deratio = Deside / Demain (i.e. the ratio of the Deborah number (De) of the sidestream to the mainstream liquids) is introduced to correlate the magnitude of energy discontinuity between the two liquids. A new Deratio-Demain operating space diagram was constructed to present the observation of the effects of both elasticity and energy discontinuity in a compact manner, and for a general classification of the states of flow development.